Coverlay Film
The coverlay film, featuring a polyimide film and an epoxy adhesive layer with nylon resin, addresses the challenges of efficient etching and reduced side etching, enabling the production of flexible printed wiring boards with small openings while maintaining strong adhesive properties.
Patent Information
- Application Number
- JP2021052110
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-25
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-03-25
AI Technical Summary
Existing coverlay films face challenges in efficiently etching the adhesive layer while minimizing side etching, particularly when using epoxy adhesives with polyimide films, which affects the manufacturing of flexible printed wiring boards with small openings.
A coverlay film comprising a polyimide film and an adhesive layer with an epoxy resin, where the adhesive layer includes a specific component, such as nylon resin, that allows for efficient etching and reduced side etching, while maintaining adequate adhesive strength to the metal laminate.
The proposed coverlay film enables efficient etching of the adhesive layer with minimal side etching, allowing for the manufacture of flexible printed wiring boards with small openings and maintaining the same adhesive strength as conventional coverlay films.
Smart Images

Figure 0007671608000003 
Figure 0007671608000004 
Figure 0007671608000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a coverlay film that is useful for etching and the like. [Background technology]
[0002] Flexible printed circuit boards (hereinafter also referred to as "FPC") are formed by protecting the surface of a metal laminate such as a copper-clad laminate with a coverlay film. The coverlay film is usually formed of an insulating layer such as a polyimide film and an adhesive layer, and covers the metal laminate via the adhesive layer.
[0003] Conventionally, the covering method has been to align a coverlay film, which has openings formed by mechanical processing using a mold or the like, with the circuit surface of the metal laminate, and then bond them together by applying heat and pressure. However, such a method has problems such as the inability to form small openings (for example, openings with a diameter of less than 1000 μm).
[0004] Under these circumstances, a method using etching is being considered as another coating method. For example, Patent Document 1 describes a method in which a coverlay film, in which an adhesive that can be etched with a polyimide etching agent is applied to a polyimide film, is bonded to a copper-clad laminate, a resist layer of a desired pattern is formed on the coverlay film, and the coverlay film is etched away with a polyimide etching agent. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Special Publication No. 5-62836 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a novel coverlay film.
[0007] Another object of the present invention is to provide a coverlay film that can be efficiently etched.
[0008] Another object of the present invention is to provide a coverlay film which can reduce the amount of side etching of the adhesive layer. [Means for solving the problem]
[0009] When etching a coverlay film, etching the adhesive layer can be difficult, especially when an epoxy adhesive is used. In particular, in a coverlay film formed of a polyimide film and an epoxy-based adhesive layer, there are cases where etching of the adhesive layer cannot be performed even if etching of the polyimide film can be performed. Even if etching of the epoxy-based adhesive layer can be performed, there is a problem that the etching solution or etching gas penetrates to the interface between the polyimide film and the adhesive layer, resulting in a side etching portion that is etched larger than the intended etching portion. On the other hand, there is a problem that etching of the adhesive layer becomes difficult when trying to improve the adhesion between the polyimide film and the epoxy-based adhesive layer. Thus, in a coverlay film using a polyimide film, it is difficult to both etch the adhesive layer and reduce the amount of side etching of the adhesive layer. Furthermore, the coverlay film is also required to have adhesive strength between the adhesive layer and the metal laminate, but it has been difficult to achieve both the etching of the adhesive layer and the required adhesive strength.
[0010] In this situation, the present inventors have found that a coverlay film in which an epoxy adhesive containing a specific component is applied to a polyimide film can not only efficiently etch the adhesive layer, but also reduce the amount of side etching of the adhesive layer. The present inventors have also found that such a coverlay film can bond the adhesive layer to a metal laminate with an adhesive strength equivalent to that of a conventional coverlay film. The present inventors have further conducted research and have completed the present invention.
[0011] The present invention relates to the following coverlay film, etc. [1] A coverlay film for etching formed of a polyimide film and an adhesive layer, the adhesive layer being etchable, and the adhesive comprising an epoxy resin. [2] A coverlay film constituting a flexible printed wiring board including a coverlay film and a metal laminate, the coverlay film is formed of a polyimide film and an adhesive layer, the adhesive forming the adhesive layer contains an epoxy resin; A coverlay film in which the coverlay film is etched, and the amount of side etching of the adhesive layer is 30% or less of the etching width. [3] The coverlay film according to [1] or [2], wherein the adhesive forming the adhesive layer contains a nylon resin. [4] The coverlay film according to [3], wherein the content of the nylon resin is 15 to 95 parts by mass per 100 parts by mass of the adhesive. [5] The coverlay film according to any one of [1] to [4], wherein the adhesive layer has a thickness of 5 to 30 μm. [6] The coverlay film according to any one of [1] to [5], wherein the polyimide film has a thickness of 5 to 40 μm. [7] The coverlay film according to any one of [1] to [6], wherein the polyimide film contains, as raw materials, an aromatic diamine component containing paraphenylenediamine and 4,4'-diaminodiphenyl ether, and an aromatic acid anhydride component containing pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride, in which the molar ratio of paraphenylenediamine to 4,4'-diaminodiphenyl ether is 45 / 55 to 1 / 99, and the molar ratio of pyromellitic dianhydride to 3,3',4,4'-biphenyltetracarboxylic dianhydride is 95 / 5 to 50 / 50. [8] The coverlay film according to any one of [1] to [7], which is for use in wet etching. [9] A flexible printed wiring board using the coverlay film according to any one of [1] to [8].
[10] The flexible printed wiring board according to [9], wherein the amount of side etching of the adhesive layer relative to the opening of the flexible printed wiring board is 30% or less.
[11] The flexible printed wiring board according to [9] or
[10] , wherein the amount of side etching of the polyimide film relative to the opening of the flexible printed wiring board is 30% or less.
[12] A method for producing a flexible printed wiring board, comprising the steps of: laminating the coverlay film according to any one of [1] to [8] to a metal laminate; etching a polyimide film of the coverlay film; and etching an adhesive layer of the coverlay film. Effect of the Invention
[0012] According to the present invention, a novel coverlay film can be provided.
[0013] According to another aspect of the present invention, a coverlay film that can be efficiently etched can be provided.
[0014] According to another aspect of the present invention, a coverlay film capable of efficiently etching an adhesive layer can be provided, and such a coverlay film can reduce the amount of side etching (or the side etching width) of the adhesive layer.
[0015] According to another aspect of the present invention, a coverlay film capable of efficiently etching a polyimide film can be provided, and the amount of side etching of the polyimide film can be reduced using such a coverlay film.
[0016] According to another aspect of the present invention, it is possible to provide a coverlay film that can be adhered to a metal laminate plate with adhesive strength equivalent to that of conventional coverlay films.
[0017] According to another aspect of the present invention, since the coverlay film can be etched, a flexible printed wiring board having small openings (eg, openings with a diameter of less than 1000 μm) formed therein can be manufactured. [Brief description of the drawings]
[0018] [Figure 1] FIG. 13 is a view of a hole portion of a sample after etching of the adhesive layer in an example, viewed from above on the coverlay film side. [Diagram 2] 2 is a cross-sectional view taken along the line XX in FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The coverlay film of the present invention is formed of a polyimide film and an adhesive layer (or an adhesive layer is laminated on a polyimide film). Such a coverlay film usually has an adhesive layer on one side of the polyimide film. In the coverlay film of the present invention, the adhesive that forms the adhesive layer usually contains an epoxy resin.
[0020] [Polyimide film] Polyimide films usually contain an aromatic diamine component and an aromatic acid anhydride component as raw materials.
[0021] The aromatic diamine component may contain, for example, at least paraphenylenediamine and / or 4,4'-diaminodiphenyl ether. When the aromatic diamine component contains paraphenylenediamine and 4,4'-diaminodiphenyl ether, from the viewpoint of easily and efficiently etching the coverlay film, the molar ratio of paraphenylenediamine to 4,4'-diaminodiphenyl ether may be, for example, about 50 / 50 to 1 / 99 (e.g., 45 / 55 to 1 / 99), preferably about 40 / 60 to 1 / 99 (e.g., 35 / 65 to 3 / 97).
[0022] The aromatic acid anhydride component may contain, for example, at least pyromellitic dianhydride and / or 3,3',4,4'-biphenyltetracarboxylic dianhydride. When the aromatic acid anhydride component contains pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride, from the viewpoint of easily and efficiently etching the coverlay film, the molar ratio of pyromellitic dianhydride to 3,3',4,4'-biphenyltetracarboxylic dianhydride may be, for example, about 99 / 1 to 40 / 60 (e.g., 97 / 3 to 45 / 55), preferably about 96 / 4 to 50 / 50 (e.g., 95 / 5 to 60 / 40).
[0023] The aromatic diamine component may contain an aromatic diamine component other than paraphenylenediamine and 4,4'-diaminodiphenyl ether. Other aromatic diamine components include 3,3'-diaminodiphenyl ether, metaphenylenediamine, diaminodiphenylpropane (e.g., 4,4'-diaminodiphenylpropane, 3,4'-diaminodiphenylpropane, 3,3'-diaminodiphenylpropane, etc.), diaminodiphenylmethane (e.g., 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, etc.), benzidine, diaminodiphenyl diaminodiphenyl sulfide (e.g., 4,4'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfide, etc.), diaminodiphenyl sulfone (e.g., 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, etc.), 2,6-diaminopyridine, bis-(4-aminophenyl)diethylsilane, 3,3'-dichlorobenzidine, bis-( 4-aminophenyl)ethyl phosphinoxide, bis-(4-aminophenyl)phenyl phosphinoxide, bis-(4-aminophenyl)-N-phenylamine, bis-(4-aminophenyl)-N-methylamine, 1,5-diaminonaphthalene, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,4'-dimethyl-3',4-diaminobiphenyl, 3,3'-dimethoxybenzidine, 2,4-bis(p-β-amino-t-butylphenyl)ether, bis Examples of such compounds include (p-β-amino-t-butylphenyl) ether, p-bis(2-methyl-4-aminopentyl)benzene, p-bis-(1,1-dimethyl-5-aminopentyl)benzene, m-xylylenediamine, p-xylylenediamine, 2,5-diamino-1,3,4-oxadiazole, 2,2-bis(4-aminophenyl)hexafluoropropane, N-(3-aminophenyl)-4-aminobenzamide, 4-aminophenyl-3-aminobenzoate, etc. These compounds can be used alone or in combination of two or more.
[0024] The raw material components of the polyimide film may contain diamine components other than the above aromatic diamine components, as long as the effects of the present invention are not impaired. Examples of other diamine components include diaminoadamantanes (e.g., 1,3-diaminoadamantane, 3,3'-diamino-1,1'-diaminoadamantane, 3,3'-diaminomethyl-1,1'-diadamantane, etc.), diaminoalkanes (e.g., hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, 3-methylheptamethylenediamine, 4,4'-dimethylheptamethylenediamine, 2,11-diaminododecane, 2,2-dimethylpropylenediamine, etc.), amine, 3-methoxyhexaethylenediamine, 2,5-dimethylhexamethylenediamine, 2,5-dimethylheptamethylenediamine, 5-methylnonamethylenediamine, 1,4-diaminocyclohexane, 1,12-diaminooctadecane, etc.), 1,2-bis(3-aminopropoxy)ethane, 2,5-diamino-1,3,4-oxadiazole, 2,2-bis(4-aminophenyl)hexafluoropropane, N-(3-aminophenyl)-4-aminobenzamide, 4-aminophenyl-3-aminobenzoate, etc. These can be used alone or in combination of two or more.
[0025] The aromatic acid anhydride component may contain an aromatic acid anhydride component other than pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride. Examples of other aromatic acid anhydride components include 2,3',3,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,3,6,7-naphthalenedicarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)ether, pyridine-2,3,5,6-tetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride (e.g., 1,2,4,5-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,4,5,8-decahydronaphthalenetetracarboxylic dianhydride, 4,8-dimethyl-1,2,5,6-hexahydronaphthalenetetracarboxylic dianhydride, 2,6-dichloro-1,4,5,8-naphthalenetetracarboxylic dianhydride, 2 ,7-dichloro-1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-tetrachloro-1,4,5,8-naphthalenetetracarboxylic dianhydride), 1,8,9,10-phenanthrenetetracarboxylic dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, benzene-1,2,3,4-tetracarboxylic dianhydride, 3,4,3',4'-benzophenonetetracarboxylic dianhydride, etc. These can be used alone or in combination of two or more.
[0026] Particularly preferred combinations of aromatic diamine components and aromatic acid anhydride components, from the viewpoint of easily maintaining adhesion to the adhesive layer even after etching of the adhesive layer, include, for example, a combination containing paraphenylenediamine and 4,4'-diaminodiphenyl ether in a molar ratio of 50 / 50 to 1 / 99 (preferably, 45 / 55 to 1 / 99) as the aromatic diamine components, and pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride in a molar ratio of 99 / 1 to 40 / 60 (preferably, 95 / 5 to 50 / 50) as the aromatic acid anhydride components.
[0027] [Inorganic particles] The polyimide film usually contains inorganic particles, which are usually dispersed in the polyimide film. The inorganic particles to be dispersed include, for example, oxides {e.g., SiO 2 (Silica), TiO 2 (titanium(IV) oxide), etc.}, inorganic acid salts {e.g., CaHPO 4 (Calcium hydrogen phosphate), CaPO 4 (Calcium phosphate), Ca 2 P 2 O 7 (Calcium diphosphate) and other (hydrogen) phosphates, CaCO 3 (Calcium carbonate, etc.)}. The inorganic particles may be used alone or in combination of two or more kinds.
[0028] The average particle size of the inorganic particles to be dispersed may be, for example, 0.5 to 2.2 μm, preferably 0.5 to 2.0 μm, and more preferably 0.5 to 1.9 μm. The method for measuring the average particle size of the inorganic particles is not particularly limited, and any known method may be used.
[0029] The particle size distribution of the inorganic particles to be dispersed is preferably narrow, that is, the proportion of inorganic particles of similar size to the total inorganic particles is preferably high. For example, particles with a particle diameter of 0.5 to 2.5 μm may account for 80 volume % or more (e.g., 80 to 100 volume %) of the total inorganic particles. The method for measuring the particle size distribution of the inorganic particles is not particularly limited, and a known method may be used.
[0030] The polyimide film may contain additives other than inorganic particles (for example, pigments, matting agents, etc.) The additives may be used alone or in combination of two or more. The pigment is not particularly limited, but examples thereof include black pigments {eg, aniline black, black composite oxide pigments (CICP), etc.}. The matting agent is not particularly limited, but examples thereof include ceramic materials {eg, borides, nitrides, carbides, oxides (eg, alumina, titanium oxide, silica, etc.)} and the like.
[0031] When the pigment or matting agent is in particulate form, the average particle size of the pigment particles or matting agent particles to be dispersed may be, for example, 0.5 to 7.0 μm, preferably 0.5 to 6.8 μm, and more preferably 0.5 to 6.5 μm. The method for measuring the average particle size of the particles is not particularly limited, and any known method may be used.
[0032] When the pigment or matting agent is in particulate form, the particle size distribution of the pigment particles or matting agent particles to be dispersed may be the same as the particle size distribution of the inorganic particles described above.
[0033] Although the reason is unclear, polyimide films containing particles (e.g., inorganic particles, pigment particles, matting agent particles, etc.) tend to improve adhesion to the adhesive layer. When polyimide films contain particles, unevenness is formed on the surface of the polyimide film, and it is assumed that the adhesive penetrates into the uneven parts, making it easier to improve adhesion between the polyimide film and the adhesive layer.
[0034] [Manufacturing method of polyimide film] Next, a method for producing a polyimide film will be described. In obtaining a polyimide film, first, a component containing an aromatic diamine component and an aromatic acid anhydride component is polymerized in an organic solvent to obtain a polyamic acid solution (hereinafter, also referred to as a polyamic acid solution).
[0035] Specific examples of organic solvents used to form the polyamic acid solution include sulfoxide-based solvents such as dimethyl sulfoxide and diethyl sulfoxide, formamide-based solvents such as N,N-dimethylformamide and N,N-diethylformamide, acetamide-based solvents such as N,N-dimethylacetamide and N,N-diethylacetamide, pyrrolidone-based solvents such as N-methyl-2-pyrrolidone and N-vinyl-2-pyrrolidone, phenol-based solvents such as phenol, o-, m-, or p-cresol, xylenol, halogenated phenols, and catechol, and aprotic polar solvents such as hexamethylphosphoramide and γ-butyrolactone. These may be used alone or in combination of two or more. Furthermore, they may be used in combination with aromatic hydrocarbons such as xylene and toluene.
[0036] The polymerization method of the polyamic acid solution may be any known method, for example, (1) A method in which the entire amount of the aromatic diamine component is first placed in a solvent, and then the aromatic acid anhydride component is added in an amount equivalent to the entire amount of the aromatic diamine component to polymerize the mixture. (2) A method in which the entire amount of the aromatic acid anhydride component is first placed in a solvent, and then the aromatic diamine component is added in an amount equivalent to the amount of the aromatic acid anhydride component to polymerize the resulting mixture. (3) A method of polymerizing by adding one aromatic diamine component to a solvent, mixing one aromatic acid anhydride component in a ratio of 95 to 105 mol % relative to the reaction components for a time required for reaction, adding the other aromatic diamine component, and then adding the other aromatic acid anhydride component so that the total aromatic diamine component and the total aromatic acid anhydride component are approximately equivalent in weight, (4) A method in which one aromatic acid anhydride component is placed in a solvent, and then mixed for a time required for reaction in a ratio of one aromatic diamine component to the reaction components such that the ratio is 95 to 105 mol % relative to the reaction components, and then the other aromatic acid anhydride component is added, and then the other aromatic diamine component is added so that the total aromatic diamine component and the total aromatic acid anhydride component are approximately equivalent in weight, thereby polymerizing the mixture; (5) A method of preparing a polyamic acid solution (A) by reacting one aromatic diamine component with an aromatic acid anhydride component in a solvent so that one is in excess, and preparing a polyamic acid solution (B) by reacting the other aromatic diamine component with an aromatic acid anhydride component in another solvent so that one is in excess. The polyamic acid solutions (A) and (B) thus obtained are mixed to complete the polymerization. At this time, when the aromatic diamine component is in excess when preparing the polyamic acid solution (A), the aromatic acid anhydride component is in excess in the polyamic acid solution (B), and when the aromatic acid anhydride component is in excess in the polyamic acid solution (A), the aromatic diamine component is in excess in the polyamic acid solution (B), and the polyamic acid solutions (A) and (B) are mixed together to adjust so that the total aromatic diamine component and the total aromatic acid anhydride component used in these reactions are approximately equivalent. The polymerization method is not limited to these, and other known methods may be used.
[0037] The aromatic acid anhydride component and aromatic diamine component that constitute the polyamic acid are polymerized in a ratio such that the number of moles of each is approximately equal, but one may be blended in excess of the other within a range of 10 mol %, preferably 5 mol %.
[0038] The polymerization reaction is preferably carried out in an organic solvent while stirring. The polymerization temperature is not particularly limited, but is usually carried out at an internal temperature of 0 to 80°C of the reaction solution. The polymerization time is not particularly limited, but is preferably carried out continuously for 10 minutes to 30 hours. The polymerization reaction may be divided or the temperature may be increased or decreased as necessary. There is no particular restriction on the order of addition of both reactants, but it is preferable to add the aromatic acid anhydride to the solution of the aromatic diamine component. Vacuum degassing during the polymerization reaction is an effective method for producing a high-quality organic solvent solution of polyamic acid. The polymerization reaction may be controlled by adding a small amount of a terminal blocking agent to the aromatic diamines before the polymerization reaction. The terminal blocking agent is not particularly limited, and a known agent can be used.
[0039] The polyamic acid solution thus obtained contains a solid content of usually 5 to 40% by weight, preferably 10 to 30% by weight. The viscosity is not particularly limited, but is usually 10 to 2000 Pa·s as measured by a Brookfield viscometer, and is preferably 100 to 1000 Pa·s for stable liquid transfer. The polyamic acid in the organic solvent solution may be partially imidized.
[0040] The polyamic acid solution usually contains inorganic particles. When obtaining a polyamic acid solution containing inorganic particles, the inorganic particles may be added to a polyamic acid solution that has been polymerized in advance, or the polyamic acid solution may be polymerized in the presence of the inorganic particles.
[0041] It is preferable to use the inorganic particles as a slurry (inorganic particle slurry) dispersed in a solvent (e.g., a polar solvent such as N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, or N-methylpyrrolidone) because this can prevent aggregation.
[0042] The method for producing the inorganic particle slurry is not particularly limited, and may be a conventionally known method. For example, the method for producing the inorganic particle slurry may be a method of mixing inorganic particles and a solvent using a mixer. As the mixer, it is preferable to use a mixer with high shear force such as a high-speed disperser, a homomixer, a ball mill, a coalesce mixer, or a stirring disperser. In addition, a wet grinding process may be performed to reduce the average particle size. For example, a bead mill, a sand mill, or the like may be used for the wet grinding process.
[0043] The inorganic particle slurry may be a commercially available product in which inorganic particles are dispersed in a solvent in advance. The inorganic particle slurry may contain other organic solvents, compounding agents, and the like, as necessary.
[0044] The concentration of the inorganic particles in the inorganic particle slurry is not particularly limited, but is, for example, 1 to 80% by weight, preferably 1 to 60% by weight, and more preferably 1 to 40% by weight.
[0045] The amount of inorganic particles added may be an amount that, when the polyimide is formed, is usually 0.05 to 0.8% by weight, preferably 0.05 to 0.55% by weight, more preferably 0.05 to 0.52% by weight, and particularly preferably 0.05 to 0.5% by weight per weight of the polyimide resin solid content.
[0046] The polyamic acid solution may contain a pigment or a matting agent. The polyamic acid solution containing a pigment or a matting agent may be obtained in the same manner as the polyamic acid solution containing inorganic particles described above. The pigment slurry or the matting agent slurry may be the same as the inorganic particle slurry described above.
[0047] The amount of pigment added may be, for example, 1 to 30% by weight, preferably 1.3 to 25% by weight, and more preferably 1.5 to 24% by weight, per weight of the polyimide resin solid content when the polyimide is formed.
[0048] The amount of the matting agent added may be, for example, 0.5 to 15% by weight, preferably 0.6 to 13% by weight, and more preferably 0.6 to 12% by weight, per weight of the polyimide resin solid content when the polyimide is formed.
[0049] Methods for producing a polyimide film include, for example, a method in which a polyamic acid solution is cast into a film and thermally decyclized and desolvated to obtain a polyimide film, and a method in which a cyclization catalyst and a dehydrating agent are mixed into a polyamic acid solution and chemically decyclized to produce a gel film, which is then heated and desolvated to obtain a polyimide film.
[0050] In the chemical decyclization method, the polyamic acid solution is first prepared. The polyamic acid solution may contain a cyclization catalyst (imidization catalyst), a dehydrating agent, a gelation retarder, and the like.
[0051] Specific examples of the cyclization catalyst include aliphatic tertiary amines such as trimethylamine and triethylenediamine, aromatic tertiary amines such as dimethylaniline, and heterocyclic tertiary amines such as isoquinoline, pyridine, and β-picoline, which can be used alone or in combination of two or more. Among these, an embodiment using at least one heterocyclic tertiary amine is preferred.
[0052] Specific examples of the dehydrating agent include aliphatic carboxylic acid anhydrides such as acetic anhydride, propionic anhydride, and butyric anhydride, and aromatic carboxylic acid anhydrides such as benzoic anhydride, with acetic anhydride and / or benzoic anhydride being preferred.
[0053] A method for producing a polyimide film from a polyamic acid solution can be exemplified by a method in which a polyamic acid solution containing a cyclization catalyst and a dehydrating agent is cast onto a support from a slitted die or the like to form a film, and imidization is partially allowed to proceed on the support to form a gel film having self-supporting properties, which is then peeled off from the support and subjected to a heat treatment to obtain a polyimide film.
[0054] The polyamic acid solution is cast onto a heated support, where it undergoes a thermal ring-closing reaction to become a self-supporting gel film, which is then peeled off from the support.
[0055] The support is a metallic rotating drum or endless belt, and its temperature is controlled by a liquid or gas heat medium and / or radiant heat from an electric heater or the like.
[0056] The gel film is heated, usually to 30 to 200°C, preferably 40 to 150°C, by receiving heat from the support and / or from a heat source such as hot air or an electric heater, to cause a ring-closing reaction, and the released volatile components such as organic solvent are dried, thereby making the gel film self-supporting and allowing it to be peeled off from the support.
[0057] The gel film peeled off from the support may be stretched in the running direction while controlling the running speed with a rotating roll. The stretching temperature may be, for example, 140° C. or less. The stretching ratio may be, for example, 1.01 to 1.90 times, preferably 1.05 to 1.60 times, and more preferably 1.10 to 1.50 times. The gel film stretched in the running direction may be introduced into a tenter device, and stretched in the width direction while holding both ends in the width direction with tenter clips and running together with the tenter clips.
[0058] The stretched gel film may be heated for 15 seconds to 30 minutes using wind, an infrared heater, etc. Then, it may be heat-treated for 15 seconds to 30 minutes at a temperature of, for example, 250 to 550° C. using hot wind and / or an electric heater, etc.
[0059] The thickness of the polyimide film may be adjusted by adjusting the running speed.
[0060] The polyimide film thus obtained may be further annealed. The annealing method is not particularly limited and may be performed according to a conventional method. The annealing temperature is not particularly limited, but may be, for example, 200 to 500°C, preferably 200 to 370°C, and more preferably 210 to 350°C. Specifically, the annealing may be performed by running the film under low tension in a furnace heated to the above temperature range. The tension of the film during running may be, for example, 10 to 50 N / m, and more preferably 20 to 30 N / m.
[0061] The thickness (average thickness) of the polyimide film obtained as described above may be, for example, about 1 to 150 μm (e.g., 1 to 125 μm), preferably about 3 to 100 μm (e.g., 3 to 80 μm), and more preferably about 5 to 80 μm (e.g., 7 to 50 μm, 10 to 40 μm, 5 to 40 μm, etc.).
[0062] [Adhesive layer] The adhesive that forms the adhesive layer typically includes an adhesive component. The adhesive component may typically include an epoxy resin. The adhesive layer may also be an etchable layer. The etching may be dry etching, wet etching, etc., preferably wet etching.
[0063] The epoxy resin is not particularly limited, and a general-purpose epoxy resin may be used, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenol novolac type epoxy resin, cresol novolac type epoxy resin, glycidylamine type epoxy resin, etc. The epoxy resin may be modified. The epoxy resin may be used alone or in combination of two or more. The epoxy resin may be solid or liquid.
[0064] The epoxy equivalent of the epoxy resin is not particularly limited, but may be, for example, about 500 g / equivalent or less, preferably 400 g / equivalent or less, and more preferably 300 g / equivalent or less.
[0065] The adhesive component may contain a polyamide resin from the viewpoints of efficient etching (particularly, efficient formation of an adhesive layer that can be etched from the adhesive) and the balance between ease of etching and adhesive ability. The reason why etching can be carried out efficiently when the adhesive component contains a polyamide resin is not clear, but it is speculated that, particularly in etching of the adhesive layer (particularly wet etching, which will be described later), the amide groups of the polyamide resin are hydrolyzed by the etching solution for the adhesive layer, making it easier for etching to proceed.
[0066] The polyamide resin may be, for example, a condensation polymer of a diamine and a dicarboxylic acid, a ring-opening polymer of a cyclic amide compound, a condensation polymer of an amino acid, etc. The polyamide resin may contain either an aliphatic skeleton or an aromatic skeleton, or may contain both. The polyamide resin may be used alone or in combination of two or more kinds. The method for producing the polyamide resin is not particularly limited, and a known method may be used.
[0067] Examples of diamines include aliphatic diamines [for example, linear or branched aliphatic diamines (e.g., ethylenediamine, tetramethylenediamine, hexamethylenediamine, heptamethylenediamine, nonanediamine, etc.), alicyclic diamines (e.g., isophoronediamine, etc.)], aromatic diamines (e.g., xylylenediamine, piperazine, etc.), etc. The diamines may be used alone or in combination of two or more.
[0068] Examples of dicarboxylic acids include aliphatic dicarboxylic acids (e.g., adipic acid, azelaic acid, sebacic acid, undecanoic acid, dodecanedioic acid, dimer acid, etc.), aromatic dicarboxylic acids (e.g., isophthalic acid, terephthalic acid, etc.), etc. The dicarboxylic acids may be used alone or in combination of two or more.
[0069] Examples of the cyclic amide compound include β-lactam, ε-caprolactam, laurinlactam, α-pyrrolidone, α-piperidone, etc. The cyclic amide compound may be used alone or in combination of two or more kinds.
[0070] Examples of the amino acid include aliphatic amino acids [for example, linear or branched aliphatic amino acids (for example, 11-aminoundecanoic acid, 12-aminododecanoic acid, etc.), alicyclic amino acids (for example, 4-aminomethylcyclohexanecarboxylic acid, etc.)], aromatic amino acids (for example, 4-aminomethylbenzoic acid, etc.), etc. The amino acids may be used alone or in combination of two or more.
[0071] The polyamide resin may suitably be a polyamide resin (or a nylon resin) containing a primarily aliphatic backbone.
[0072] The nylon resin is not particularly limited, and may be, for example, a condensation polymer of a diamine including an aliphatic diamine and a dicarboxylic acid including an aliphatic dicarboxylic acid, a ring-opening polymer of a cyclic amide compound, or a condensation polymer of an amino acid including an aliphatic amino acid.
[0073] The nylon resin may function as a hardener for the epoxy resin. The acid value of the nylon resin may be, for example, 4 to 10 mgKOH / g, from the viewpoints of reactivity with the epoxy resin and ease of efficiently etching the adhesive layer. The amine value of the nylon resin may be, for example, 1 to 6 mgKOH / g, from the viewpoints of reactivity with the epoxy resin and ease of efficiently etching the adhesive layer. The acid value may be the number of milligrams of KOH required to neutralize the acid present in 1 g of resin, and the amine value may be the number of milligrams of KOH equivalent to hydrochloric acid required to neutralize the amine present in 1 g of resin. The method for measuring the acid value is not particularly limited, but for example, the method described below may be used. The method for measuring the amine value is not particularly limited, but for example, the method described below may be used.
[0074] The adhesive component may include a hardener for the epoxy resin. The epoxy resin curing agent may be a general-purpose component, such as amines [for example, aliphatic polyamines (e.g., diethylenetriamine, triethylenetetramine, etc.), aromatic polyamines (e.g., metaphenylenediamine, diaminodiphenylmethane, diaminodiphenylsulfone, etc.)], acid anhydrides [for example, cyclic aliphatic acid anhydrides (e.g., methyltetrahydrophthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, etc.)], etc. These curing agents may be modified. The epoxy resin curing agent may be used alone or in combination of two or more. The polyamide resin may also function as a curing agent.
[0075] The adhesive (or adhesive layer) may contain adhesive components other than the epoxy resin, polyamide resin, and epoxy resin curing agent, as long as the effects of the present invention are achieved. The other adhesive components are not particularly limited, but examples thereof include thermoplastic resins other than those exemplified above (e.g., phenoxy resin, etc.), thermosetting resins, etc. The other adhesive components may be used alone or in combination of two or more.
[0076] The adhesive (or adhesive layer) may contain additives other than the adhesive component as long as the effects of the present invention are achieved. Examples of the additives include coupling agents, flame retardants (or flame retardant assistants), antioxidants, ultraviolet absorbers, fillers, leveling agents, and defoamers.
[0077] The coupling agent may be a general-purpose component, for example, a silane-based coupling agent {for example, a vinyl group-containing silane (for example, vinyltrimethoxysilane, etc.), an epoxy group-containing silane (for example, 3-glycidoxypropyltrimethoxysilane, etc.), a (meth)acryloyl group-containing silane (for example, 3-methacryloxypropylmethyldimethoxysilane, 3-acryloxypropyltrimethoxysilane, etc.), an amino group-containing silane [for example, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, methoxysilane, etc.], mercapto group-containing silanes (e.g., 3-mercaptopropylmethyldimethoxysilane, etc.), styryl group-containing silanes (e.g., p-styryltrimethoxysilane, etc.), ureido group-containing silanes (e.g., 3-ureidopropyltriethoxysilane, etc.), isocyanate group-containing silanes (e.g., 3-isocyanatopropyltriethoxysilane, etc.), etc.}, titanate-based coupling agents, aluminate-based coupling agents, zirconium-based coupling agents, etc.
[0078] Examples of the flame retardant (including flame retardant auxiliary) include general-purpose components such as metal hydrates [for example, metal hydroxides (for example, magnesium hydroxide, aluminum hydroxide, calcium hydroxide, barium hydroxide, etc.), tin oxide hydrate, basic magnesium carbonate, etc.], halogen-based compounds {for example, halogen-containing low molecular weight compounds (decabromodiphenyl ether, halogenated bisphenol A, etc.), halogen-containing resins [for example, epoxy resins (brominated epoxy resins, etc.)], etc.}, antimony-based compounds (for example, antimony trioxide, etc.), phosphorus-based compounds (for example, phosphorus-containing oligomers, ammonium phosphate, aluminum trisdiphenylphosphinate, etc.), etc.
[0079] Examples of the antioxidant include general-purpose components such as phenolic compounds [e.g., 2,6-di-t-butyl-4-methylphenol, n-octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, etc.] and phosphorus-based compounds [e.g., trisnonylphenyl phosphite, tris(2,4-di-t-butylphenyl)phosphite, etc.].
[0080] Examples of the ultraviolet absorbing agent include general-purpose components, such as benzotriazole-based ultraviolet absorbing agents [e.g., 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-[(2'-hydroxy-3',5'-bis(α,α-dimethylbenzyl)phenyl]-benzotriazole, etc.], benzophenone-based ultraviolet absorbing agents (e.g., 2,4-dihydroxybenzophenone, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octylbenzophenone, etc.), and salicylate-based ultraviolet absorbing agents. agents (e.g., phenyl salicylate, etc.), cyanoacrylate-based ultraviolet absorbers (e.g., ethyl-2-cyano-3,3-diphenylacrylate, etc.), oxalic anilide-based ultraviolet absorbers (e.g., 2-ethoxy-2'-ethyl oxalic acid bisanilide, etc.), hindered amine-based ultraviolet absorbers (e.g., bis-[2,2,6,6-tetramethyl-4-piperidineyl]sebacate, bis-[N-methyl-2,2,6,6-tetramethyl-4-piperidinyl]sebacate, etc.).
[0081] The adhesive may contain a solvent. For example, the adhesive may be formed by mixing the adhesive components (and, if necessary, additives) with a solvent. The solvent is not particularly limited as long as it can dissolve the adhesive component, but examples thereof include alcohol-based solvents (e.g., methanol, ethanol, i-propyl alcohol, n-propyl alcohol, i-butyl alcohol, n-butyl alcohol, benzyl alcohol, ethylene glycol methyl ether, propylene glycol methyl ether, diethylene glycol monomethyl ether, diacetone alcohol, etc.), ketone-based solvents (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, methyl amyl ketone, cyclohexanone, etc.), aromatic hydrocarbon-based solvents (e.g., toluene, xylene, ethylbenzene, mesitylene, etc.), ester-based solvents (e.g., methyl acetate, ethyl acetate, ethylene glycol monomethyl ether acetate, 3-methoxybutyl acetate, etc.), chlorine-based solvents (e.g., chloroform, carbon tetrachloride, dichloromethane, trichloroethylene, etc.), etc. The solvents may be used alone or in combination of two or more. The solvent may contain components other than those exemplified above (eg, water, phenol, formic acid, acetic acid, etc.) within the range in which the adhesive component dissolves.
[0082] The solvent may suitably contain an alcohol-based solvent, for example, a combination of an alcohol-based solvent with one or more selected from a ketone-based solvent, an aromatic hydrocarbon-based solvent, an ester-based solvent, and a chlorine-based solvent.
[0083] When the solvent contains an alcohol-based solvent, the content of the alcohol-based solvent in the total solvent may be, for example, about 30 to 90 mass % (eg, 40 to 80 mass %).
[0084] In the adhesive, the content of the polyamide resin may be, for example, about 15 to 95 parts by mass, preferably about 20 to 90 parts by mass (e.g., 20 to 80 parts by mass), more preferably about 30 to 80 parts by mass (e.g., 25 to 60 parts by mass), and particularly preferably about 30 to 60 parts by mass (e.g., 30 to 50 parts by mass), per 100 parts by mass of the adhesive, from the viewpoints of making it easy to etch the adhesive layer efficiently (in particular, making it easy to reduce the amount of side etching of the adhesive layer) and making the polyimide film of the coverlay film less susceptible to the effects of etching (for example, making it easy to form good openings in the polyimide film of the coverlay film, making the polyimide film of the coverlay film more likely to reflect the thickness before etching).
[0085] In the adhesive, the mass ratio of epoxy resin to polyamide resin may be, for example, about 85:15 to 5:95, preferably 80:20 to 10:90 (for example, 75:25 to 15:85), more preferably 70:30 to 20:80 (for example, 65:35 to 25:75 parts by mass), and particularly preferably about 60:40 to 30:70, from the standpoint of making it easy to efficiently etch the adhesive layer (for example, it is easy to reduce the amount of side etching of the adhesive layer) and making the polyimide film of the coverlay film less susceptible to the effects of etching (for example, it is easy to form good openings in the polyimide film of the coverlay film and the polyimide film of the coverlay film is easy to reflect the thickness before etching).
[0086] In the adhesive, the content of the epoxy resin curing agent is not particularly limited and may be set appropriately depending on the type of epoxy resin and the type of curing agent used, etc.
[0087] In the adhesive, the content of the adhesive component may be, for example, about 1 to 99 mass % (eg, 5 to 90 mass %), and preferably about 10 to 80 mass % (eg, 15 to 70 mass %) with respect to the entire adhesive.
[0088] In the adhesive, the additive may be, for example, about 1.5 to 200 parts by mass (e.g., 2 to 170 parts by mass), preferably about 2 to 150 parts by mass (e.g., 3 to 140 parts by mass), and more preferably about 3 to 120 parts by mass (e.g., 5 to 100 parts by mass) per part by mass of the adhesive component.
[0089] [Coverlay film] The coverlay film may have an adhesive layer formed on one side of a polyimide film. The method for forming the adhesive layer is not particularly limited, and may be, for example, a method of applying an adhesive to a polyimide film and drying it. The method for applying and drying the adhesive is not particularly limited, and may be a known method.
[0090] The coverlay film may be suitable for etching. The etching may be a dry etching or a wet etching.
[0091] In the coverlay film, the thickness (average thickness) of the polyimide film is not particularly limited, but may be, for example, about 1 to 150 μm (e.g., 1 to 125 μm), preferably about 3 to 100 μm (e.g., 3 to 80 μm), and more preferably about 5 to 80 μm (e.g., 7 to 50 μm, 10 to 40 μm, 5 to 40 μm, etc.).
[0092] In the coverlay film, the thickness (average thickness) of the adhesive layer is not particularly limited, but from the viewpoint of easily reducing the amount of side etching of the adhesive layer, it may be, for example, about 50 μm or less (e.g., 1 to 45 μm), preferably 40 μm or less (e.g., 2 to 35 μm), and more preferably 30 μm or less (e.g., 5 to 30 μm).
[0093] In the coverlay film, the ratio of the thickness (average thickness) of the polyimide film to the thickness (average thickness) of the adhesive layer may be, for example, about 5:1 to 1:5, preferably 4:1 to 1:4, and more preferably about 3:1 to 1:3, from the viewpoint of making it easy to etch the coverlay film efficiently (for example, making it easy to reduce the amount of side etching of the polyimide film and the amount of side etching of the adhesive layer).
[0094] [Flexible Printed Circuits (FPC)] The coverlay film of the present invention can be used for applications such as covering metal laminates, etc. By laminating the coverlay film of the present invention to a metal laminate, a flexible printed circuit board (FPC) can be produced. That is, the present invention also includes a flexible printed wiring board using the coverlay film of the present invention. The flexible printed wiring board may include a coverlay film and a metal laminate, and the coverlay film may be laminated on the metal laminate. Such a flexible printed wiring board may have a coverlay film on one side of the metal laminate. The present invention also includes a coverlay film that constitutes a flexible printed wiring board.
[0095] The metal laminate plate may be formed of, for example, an insulating layer (e.g., a polyimide film, etc.) and a metal layer. The metal layer may be a metal foil or a metal vapor deposition film. The metal layer may be formed on one side or both sides of the insulating layer. The thickness (average thickness) of the insulating layer is not particularly limited and may be, for example, 5 to 200 μm. The thickness (average thickness) of the metal layer is not particularly limited and may be, for example, 1 to 50 μm. The metal laminate plate may have layers other than the insulating layer and the metal layer. In the metal laminate plate, the locations where the other layers are laminated are not particularly limited. The method for producing the metal laminate is not particularly limited, and any known method (e.g., a method of hot pressing a metal foil onto an insulating layer, a method of vapor-depositing a metal (e.g., vacuum vapor deposition) onto the surface of an insulating layer, etc.) may be used.
[0096] The metal constituting the metal layer is not particularly limited, but examples thereof include copper, copper alloys, stainless steel, nickel, and aluminum, and copper or copper alloys may be preferably used. As the metal laminate, a copper-clad laminate may be suitably used.
[0097] The method for producing the FPC is not particularly limited, but a method using etching is preferred. The etching may be, for example, wet etching, dry etching, or the like, with wet etching being particularly preferred.
[0098] One embodiment of the method for producing an FPC may include, for example, a step (I) of laminating the coverlay film of the present invention to a metal laminate, a step (II) of forming a resist layer on the coverlay film, a step (III) of etching the polyimide film of the coverlay film, and a step (IV) of etching the adhesive layer. Note that steps (I) to (IV) may usually be performed in this order. Before or after each step, other steps (e.g., a cleaning step, a neutralization step, etc.) may be included as necessary.
[0099] In step (I), the method for laminating the coverlay film to the metal laminate is not particularly limited, and may be a known method of thermocompression bonding, etc. Such a method is not particularly limited, and may be, for example, a method using a hot press machine, a method using a roll, etc. The temperature of thermocompression bonding is not particularly limited, and may be, for example, 50 to 200°C, etc. The pressure of thermocompression bonding is not particularly limited, and may be, for example, 1 to 10 MPa, etc. The time of thermocompression bonding is not particularly limited, and may be, for example, 1 minute to 1 hour, etc.
[0100] Step (I) may include a step of curing the adhesive layer after the lamination. The curing temperature may be appropriately set depending on the components contained in the adhesive, and may be, for example, 100 to 200° C. The curing time is not particularly limited, and may be, for example, 30 minutes to 5 hours (e.g., 1 to 3 hours).
[0101] In step (II), usually after step (I), a resist layer may be formed on the coverlay film. The resist forming the resist layer may be, for example, an ultraviolet curing resist, an alkali development resist, a heat curing resist, etc., and an ultraviolet curing resist may be preferably used. The resist may be either a dry film resist or a liquid resist, and a dry film resist may be preferably used. The resist may be either a negative type or a positive type. The resist is not particularly limited, and a known one may be used.
[0102] In forming the resist layer, the resist is usually first attached or applied onto a coverlay film, and then cured according to the type of resist. At this time, a mask having a desired pattern may be laminated on the resist before curing. The curing method is not particularly limited, and a known method may be used. For example, when an ultraviolet-curing dry film resist is used, the dry film resist may be laminated onto a coverlay film, and then a pattern mask may be laminated onto the dry film, followed by exposure to ultraviolet light to perform curing. The coverlay film of the present invention facilitates efficient production of FPCs even when a pattern mask having small openings [eg, openings less than 1000μ (eg, 500μm or less, 100μm or less)] is used.
[0103] After the curing, the uncured portion of the resist is developed and removed to form a resist layer. The developing method is not particularly limited, and may be a method using a known developer suitable for the type of resist.
[0104] The thickness (average thickness) of the resist layer is not particularly limited, and may be, for example, 5 to 50 μm (eg, 10 to 30 μm).
[0105] In step (III), the polyimide film of the coverlay film may be etched after step (II). The etching method is not particularly limited, and a known method may be used. The etching may be wet etching or dry etching.
[0106] When wet etching is performed, the substrate is immersed in an etching solution. The etching solution for polyimide film is not particularly limited as long as it is a solution capable of etching polyimide film, and commercially available polyimide etching solutions may be used. Examples of the etching solution for polyimide film include solutions containing oxyalkylamines [e.g., alkanolamines (e.g., primary alkanolamines such as ethanolamine and propanolamine; secondary alkanolamines such as diethanolamine and dipropanolamine)] and alkali metal compounds [e.g., alkali metal hydroxides (e.g., potassium hydroxide, sodium hydroxide, lithium hydroxide)]. The etching solution for the polyimide film may contain a solvent (for example, a polar organic solvent such as N-methyl-2-pyrrolidone).
[0107] When dry etching is performed, a known method such as reactive ion etching may be used.
[0108] After etching the polyimide film, the resist layer may be removed (or peeled off). The method for removing (or peeling off) the resist layer is not particularly limited, and a known method depending on the type of resist used may be used, for example, a removal (or peeling) liquid may be used.
[0109] In step (IV), the adhesive layer of the coverlay film may be etched after step (III). The etching method is not particularly limited, and a known method may be used. The etching may be wet etching or dry etching.
[0110] When wet etching is performed, the substrate is immersed in an etching solution. As an etching solution for the adhesive layer, for example, a solution containing a permanganate [for example, an alkali metal salt of permanganate (for example, potassium permanganate, sodium permanganate, etc.)] and / or sodium hydroxide may be used. The adhesive layer etchant may contain water.
[0111] In the etching solution for the adhesive layer, the concentration of the permanganate is not particularly limited, and may be, for example, about 0.5 to 50 mass % (eg, 1 to 40 mass %, 2 to 30 mass %, etc.). In the etching solution for the adhesive layer, the concentration of sodium hydroxide is not particularly limited, and may be, for example, about 0.01 to 40 mass % (eg, 0.05 to 30 mass %, 0.1 to 25 mass %, etc.).
[0112] When dry etching is performed, a known method such as reactive ion etching may be used.
[0113] In the manner described above, a flexible printed wiring board can be produced. In the present invention, the coverlay film constituting the flexible printed wiring board may be an etched one. In such a coverlay film, the adhesive layer may have a side etching amount that is, for example, 40% or less (e.g., 38% or less), preferably 35% or less (e.g., 30% or less), and more preferably 28% or less (e.g., 25% or less) of the etching width (or the target etching width (or hole diameter)).
[0114] In a coverlay film constituting a flexible printed wiring board, the amount of side etching of the polyimide film may be, for example, 40% or less (e.g., 38% or less), preferably 35% or less (e.g., 30% or less), and more preferably 28% or less (e.g., 25% or less, 20% or less) relative to the etching width [or the target etching width (or hole diameter)].
[0115] In a coverlay film constituting a flexible printed wiring board, the width (or hole diameter) of the opening in the polyimide film may be, for example, 90% or more (e.g., 93% or more), preferably 95% or more (e.g., 97% or more) of the etching width [or the target etching width (or hole diameter)], and may be, for example, 130% or less (e.g., 125% or less), preferably 125% or less (e.g., 120% or less), and more preferably 115% or less (e.g., 110% or less). In etching the coverlay film (particularly, wet etching), the polyimide film can be etched not only by etching the polyimide film itself, but also by etching the adhesive layer. On the other hand, in the coverlay film of the present invention, the adhesive layer can be efficiently etched, so that the polyimide film is less affected by the etching of the adhesive layer. Therefore, according to the coverlay film of the present invention, the difference between the width of the opening in the polyimide film and the target etching width is easily reduced.
[0116] In the coverlay film constituting a flexible printed wiring board, the thickness (average thickness) of the polyimide film may be, for example, 40% or more (e.g., 45% or more), preferably 50% or more (e.g., 55% or more), and particularly preferably 60% or more (e.g., 65% or more) of the thickness of the polyimide film in the coverlay film before forming the flexible printed wiring board (i.e., before being laminated with the metal laminate). As described above, in the coverlay film of the present invention, the adhesive layer can be efficiently etched, and therefore a reduction in the thickness of the polyimide film due to etching of the adhesive layer can be easily suppressed. That is, in the present invention, the thickness of the polyimide film in the coverlay film constituting a flexible printed wiring board is likely to reflect the thickness of the polyimide film in the coverlay film before being constituted into a flexible printed wiring board.
[0117] In a flexible printed wiring board, the amount of side etching of the adhesive layer may be, for example, 40% or less (e.g., 38% or less), preferably 35% or less (e.g., 30% or less), and more preferably 28% or less (e.g., 25% or less) relative to the opening (or the width of the opening (or the aperture diameter (hole diameter)) of the flexible printed wiring board.
[0118] In a flexible printed wiring board, the amount of side etching of the polyimide film may be, for example, 40% or less (e.g., 38% or less), preferably 35% or less (e.g., 30% or less), and more preferably 28% or less (e.g., 25% or less) relative to the opening (or the width of the opening (or the aperture diameter (hole diameter)) of the flexible printed wiring board. EXAMPLES
[0119] Next, the present invention will be described in more detail with reference to examples. However, the present invention is not limited to these examples, and many modifications can be made by those skilled in the art within the technical spirit of the present invention.
[0120] <Polyimide film thickness> Measurement was performed using a Mitutoyo Litematic (Series 318).
[0121] <Measurement of the acid value of nylon resin> 1 g of nylon resin was dissolved in 40 ml of benzyl alcohol, and a Kyoto Electronics Manufacturing Co., Ltd. automatic titration device "AT-510" was used, connected to the same company's "APB-510-20B" as a burette. Potentiometric titration was performed using a 0.01 mol / L benzyl alcohol-based KOH solution as the titration reagent, and the number of mg of KOH per 1 g of resin was calculated.
[0122] <Measurement of amine value of nylon resin> 3g of nylon resin was dissolved in a mixed solution of 20ml of 1-butanol and 20ml of toluene, and a Kyoto Electronics Co., Ltd. automatic titrator "AT-510" was used with the same company's "APB-510-01B" connected as a burette. Potentiometric titration was performed using a 0.1mol / L 2-propanol hydrochloric acid solution as the titration reagent, and the mg of hydrochloric acid and the equivalent amount of KOH per 1g of resin were calculated.
[0123] <Measurement of adhesive strength> The unetched samples thus prepared were cut to a width of 10 mm, and the adhesive strength when peeling the polyimide film from the copper foil was measured using a tensile tester (Tensilon universal testing machine, manufactured by A&D Co., Ltd.) at a tensile speed of 50 mm / min (unit: N / cm).
[0124] <Polyimide film hole diameter> The sample after the adhesive layer etching was observed with a microscope (Keyence, VHX-2000) and the diameter of the hole (opening) in the polyimide film was measured. Figure 1 shows the sample after the adhesive layer etching as seen from above the coverlay film side, in which 1 indicates the polyimide film, 2 indicates the opening in the polyimide film, 3 indicates the diameter of the opening in the polyimide film, and 4 indicates the side-etched portion in the polyimide film.
[0125] <Amount of polyimide film side etching> A cross section of the sample after etching of the adhesive layer was cut out and observed with a laser microscope (Keyence Corporation, VK-9710), and the distance at which the polyimide film was tapered was measured as the amount of side etching of the polyimide film. Figure 2 is a cross section taken along the line XX in Figure 1. In Figure 2, 5 indicates the adhesive layer, 6 indicates the copper foil, and 7 indicates the amount of side etching of the polyimide film.
[0126] <Thickness of polyimide film in sample> A cross section of the sample after adhesive etching was cut out and observed with a laser microscope (Keyence Corporation, VK-9710), and the thickness of the polyimide film was measured from the cross section.
[0127] <Side etching amount of adhesive layer> A cross section of the sample after etching of the adhesive layer was cut out and observed with a laser microscope (Keyence, VK-9710), and the distance from the tip of the taper of the polyimide film to the most etched part of the adhesive layer was measured as the amount of side etching of the adhesive layer. Note that 8 in Figure 2 indicates the amount of side etching of the adhesive layer.
[0128] Example 1 [Polyamic acid synthesis example] Pyromellitic dianhydride (PMDA) (molecular weight 218.12) / 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) (molecular weight 294.22) / 4,4'-diaminodiphenyl ether (ODA) (molecular weight 200.24) / paraphenylenediamine (PPD) (molecular weight 108.14) were prepared in a molar ratio of 65 / 35 / 80 / 20, and polymerized into a 20% by weight solution in DMAc (N,N-dimethylacetamide) to obtain a 3500 poise polyamic acid solution.
[0129] [Polyimide film production] An N,N-dimethylacetamide slurry of calcium hydrogen phosphate (average particle size: 0.87 μm, the proportion of particles with particle sizes of 0.5 to 2.5 μm in the total particles was 81.5 vol %) was added to the polyamic acid solution obtained in the above synthesis example so that the proportion of calcium hydrogen phosphate in the polyimide (film) (i.e., per weight of polyimide resin when the polyimide was formed) was 0.15 weight %, and the mixture was thoroughly stirred and dispersed. A conversion agent consisting of acetic anhydride (molecular weight 102.09) and β-picoline was mixed with this polyamic acid solution at a ratio of 2.0 molar equivalents to the polyamic acid and stirred. The resulting mixture was cast from a die onto a rotating stainless steel drum at 65°C to obtain a gel film with self-supporting properties. The gel film was peeled off from the drum, held at both ends, and treated in a heating furnace at 250°C for 30 seconds, 400°C for 30 seconds, and 550°C for 30 seconds to obtain a polyimide film with a thickness of 5 μm.
[0130] [glue] A flask equipped with a stirrer, a reflux dehydration device, and a distillation tube was charged with 65 parts by mass of azelaic acid, 190 parts by mass of dodecanedioic acid, 100 parts by mass of piperazine, and 120 parts by mass of distilled water. The temperature was raised to 120°C to distill off water, and then the temperature was raised to 240°C at a rate of 20°C / hour, and the reaction was continued for 3 hours to obtain a nylon resin. The acid value of the obtained nylon resin was 6.0 (mgKOH / g) and the amine value was 4.5 (mgKOH / g). 40 parts by mass of the obtained nylon resin, 10 parts by mass of cresol novolac epoxy resin (EPICLON N-665, manufactured by DIC Corporation) and 50 parts by mass of phenoxy resin (jER1256, manufactured by Mitsubishi Chemical Corporation) were dissolved in 400 parts by mass of a mixed solvent of ethanol / toluene=7 / 3.
[0131] [Creating coverlay film] The adhesive obtained above was applied to the polyimide film obtained above so that the thickness of the adhesive layer after drying would be 10 μm, and the film was dried at 50° C. for 2 minutes, and then further dried at 150° C. for 5 minutes.
[0132] [Sample preparation] A 35 μm-thick rolled copper foil was laminated to the coverlay film obtained above, and the film was heated and pressed at 180°C and 3 MPa for 3 minutes. The adhesive layer was then cured by heat treatment in an oven at 160°C for 2 hours to prepare a sample.
[0133] [Polyimide film etching] A dry film resist was attached to the surface of the polyimide film of the sample, and a pattern with holes of 70 μm in diameter was formed by UV exposure and alkaline development. After that, the sample was immersed in a polyimide etching solution TPE3000N manufactured by Raytec Corporation for a certain period of time to remove part of the polyimide film.
[0134] [Adhesive layer etching] After etching the polyimide film, the sample was immersed for a certain period of time in 100 g of an etching solution (solvent: water) containing sodium permanganate (8.5% by mass) and sodium hydroxide (5% by mass) to etch the adhesive layer, and then washed with water and neutralized.
[0135] (Examples 2 to 9) The same procedure was followed as in Example 1, except that the composition and thickness of the polyimide film used in the coverlay film, the content of nylon resin in the adhesive, and the thickness of the adhesive layer in the coverlay film were as shown in Table 1.
[0136] Comparative Example 1 The thickness of the polyimide film used in the coverlay film and the thickness of the adhesive layer were as shown in Table 1, and the adhesive was a solution of 20 parts by mass of cresol novolac epoxy resin (EPICLON N-665, manufactured by DIC Corporation), 60 parts by mass of phenoxy resin (jER1256, manufactured by Mitsubishi Chemical Corporation), 19.5 parts by mass of novolac type phenolic resin (TD-2106, manufactured by DIC Corporation), and 0.5 parts by mass of 2-methyl-4-methylimidazole (2E4MZ, manufactured by Shikoku Chemical Industry Co., Ltd.) dissolved in 400 parts by mass of a mixed solvent of ethanol / toluene = 7 / 3, except that the adhesive used was the same as in Example 1.
[0137] The configurations of the coverlay films of Examples 1 to 9 and Comparative Example 1 are shown in Table 1, and the evaluation results are shown in Table 2.
[0138] [Table 1]
[0139] [Table 2]
[0140] In Examples 1 to 9, the polyimide film and the adhesive layer could be etched. On the other hand, in Comparative Example 1, the polyimide film could be etched, but the adhesive layer could not be etched.
[0141] (Reference example 1) The same procedure was followed as in Example 1, except that an acrylic adhesive (Pyralux, manufactured by DuPont) was used as the adhesive instead of the adhesive used in Example 1. Although the adhesive layer could be etched, the etching speed was too fast and the adhesive layer could not be etched well. [Industrial Applicability]
[0142] The coverlay film of the present invention can be suitably used in the production of flexible printed wiring boards using etching. [Explanation of symbols]
[0143] 1 Polyimide film 2 Openings in polyimide film 3 Diameter of opening in polyimide film 4 Side etching part of polyimide film 5 Adhesive layer 6 Copper foil 7 Side etching amount of polyimide film 8 Side etching amount of adhesive layer
Claims
1. A coverlay film for etching formed of a polyimide film and an adhesive layer, the adhesive layer being etchable, and the adhesive forming the adhesive layer comprising an epoxy resin and a polyamide resin.
2. 2. The coverlay film according to claim 1, wherein the adhesive forming the adhesive layer comprises a nylon resin.
3. 3. The coverlay film according to claim 2, wherein the content of the nylon resin is 15 to 95 parts by mass per 100 parts by mass of the adhesive.
4. The coverlay film according to any one of claims 1 to 3, wherein the adhesive layer has a thickness of 5 to 30 µm.
5. The coverlay film according to any one of claims 1 to 4, wherein the polyimide film has a thickness of 5 to 40 µm.
6. The polyimide film contains, as raw materials, an aromatic diamine component containing paraphenylenediamine and 4,4'-diaminodiphenyl ether, and an aromatic acid anhydride component containing pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride, and the molar ratio of paraphenylenediamine to 4,4'-diaminodiphenyl ether is 45 / 55 to 1 / 99, and the molar ratio of pyromellitic dianhydride to 3,3',4,4'-biphenyltetracarboxylic dianhydride is 95 / 5 to 50 / 50. The coverlay film according to any one of claims 1 to 5.
7. The coverlay film according to any one of claims 1 to 6, which is for wet etching.
8. A flexible printed wiring board using the coverlay film according to any one of claims 1 to 7.
9. 9. The flexible printed wiring board according to claim 8, wherein the amount of side etching of the adhesive layer relative to the diameter of the opening of the flexible printed wiring board is 30% or less.
10. 10. The flexible printed wiring board according to claim 8, wherein the amount of side etching of the polyimide film relative to the diameter of the opening of the flexible printed wiring board is 30% or less.
11. A method for producing a flexible printed wiring board, comprising the steps of: laminating the coverlay film according to any one of claims 1 to 7 to a metal laminate; etching a polyimide film of the coverlay film; and etching an adhesive layer of the coverlay film.
Citation Information
Patent Citations
Semiconductor device and its manufacture
JP1993062836A
Adhesive for cover lay, and cover lay film
JP1995048555A
Flexible printed wiring board, cover lay film and adhesive composition
JP2000188451A
Cover lay film, flame-retardant adhesive composition of the film, and flexible printed wiring board using the composition
JP2003181993A
High turnable flexible printed wiring board
JP2007208087A